Immobilization devices used to treat unusual sites for better radiation delivery: A single institutional experience - Santosh Kumar; Rajeev Kumar; Satya Kumar; Bodhisatta Roy; Rajesh Kumar Singh; Alok Kumar (Wolters Kluwer -Medknow Publications, 2022)
The present article illustrates an attempt to design and test the reproducibility of low-cost patient positioning devices prepared in-house in the radiotherapy department. A rigid wood-polymer composite material stands with angulations, scales, and support was designed as a new method for immobilization of the mobile target using a thermoplastic mask and a carbon fiber base plate. The lower mobile target, i.e., the penis of a patient, was immobilized by this method. A computed tomography simulation was performed for the patient. This device fit was suitable, comfortable, and had good reproducibility and repeatability, which was proven in daily radiotherapy. Reproducibility and accuracy were tested by serial electronic portal imaging detectors. The positioning devices showed variations within 2-3 mm on consecutive treatment days which were within acceptable limits. It is therefore concluded that low-cost patient positioning devices for the mobile target can be fabricated from available materials in-house. With the help of these in-house available materials, we can also fabricate other types of immobilization devices for particular techniques. It is considerably cheaper than commercially available products.